Public health, policy, and clinical interventions to improve perinatal care for migrant women and infants in high-income countries: a systematic reviewResearch in context - Kerrie Stevenson; Samuel Edwards; Kemi Ogunlana; Maha Alomari; Rukayat Agoropopoola; William Henderson; Nuria Sanchez Clemente; Hannah Rayment-Jones; Majel McGranahan; Maria Marti Castaner; Serena Luchenski; Gracia Fellmeth; et al. (EClinicalMedicine)
Summary: Background: Migrant women who are pregnant or postpartum and their infants are often at increased risk of poorer perinatal outcomes compared to host country populations. This review aimed to identify public health, policy, and clinical interventions to improve maternity care for migrant women and their infants in high-income countries (HICs). Methods: In this systematic review we searched EMBASE, EMCARE, MEDLINE and PsycINFO, CENTRAL, Scopus, CINAHL Plus, Web of Science, and grey literature from inception to 13th March 2024, with no language or date restrictions (PROSPERO: CRD42022380678). Interventional and observational studies assessing the effectiveness of any intervention to improve perinatal care for migrant women and their infants in HICs delivered in the pregnancy, peripartum, or postpartum period (up to one year after birth) were included. Quantitative outcomes were extracted. Qualitative studies were excluded. The main outcomes of interest were preterm birth, birthweight, and appointment attendance. Quantitative synthesis was conducted using Harvest plots and binomial exact calculations. Findings: 15,689 records were retrieved, 29 studies comprising data from 16,763,837 women were included. 22 studies (75.9%) included multiple interventions. Five interventions had strong evidence of effectiveness. Two clinical interventions: 100.0% of studies including specialist multidisciplinary teams improved one or more of the main outcomes of interest, namely preterm birth, birthweight, and appointment attendance (95% confidence interval 73.5–100.0%; p < 0.001); and 90.9% of studies including specialist in-person interpreting improved one or more of the main outcomes of interest (58.7–100.0%; p = 0.012). Three public health or policy interventions: 100.0% of social welfare interventions (75.3%–100.0%; p < 0.001) improved one or more of the main outcomes of interest; 100.0% of maternal education interventions (71.5–100.0%. p < 0.001), and 83.3% of studies assessing access to free healthcare (51.6–97.9%; p = 0.039). Interpretation: The findings suggest that multicomponent interventions comprising multidisciplinary teams, in-person interpreting, maternal education, and social welfare support can improve perinatal outcomes for migrant women and their infants. Removing financial barriers to care may improve perinatal outcomes and be cost saving to healthcare systems. However, these findings should be interpreted with caution given that most included studies were of poor quality and that sensitivity analysis restricting to interventional studies only did not demonstrate any effect on the main outcomes of interest. Funding: KS is supported by a National Institute for Health Research (NIHR) Doctoral Fellowship (NIHR302577). HRJ is supported by an NIHR Advanced Fellowship (NIHR303183). HRJ is supported by NIHR Applied Research Collaboration (ARC) South London. MM is supported by a Medical Research Council Clinical Research Training Fellowship (Grant number MR/W01498X/1). GF is supported by a Nuffield Department of Population Health Clinical Research Fellowship. MK is an NIHR Senior Investigator (NIHR303806). The views expressed are those of the authors and not necessarily those of the NIHR or the Department of Health and Social Care.